Evolving Internationalism: Denmark and Human Rights Politics, 1948–1968. Issue 3 (3rd July 2018) - Jensen, Steven LB
ABSTRACT: The article focuses on the early phases of Denmark's engagement with international human rights after 1945 arguing that there was a closer interaction between the domestic and international spheres during these years than existing research would have us believe. This relationship did not only become a factor after a large body of international human rights law came into existence. The article offers a historical exploration of Danish human rights policies from 1948 to 1968 highlighting UN negotiations in the late 1940s and the development of the new Danish Constitution in 1953 where Denmark was struggling to adapt to the new international standards. Denmark – like the other Nordic countries – would later become what has been described as virtuous defenders of human rights but the early years show a more complex engagement. There were limits to Danish internationalism as the early human rights diplomacy was to a large extent concerned with pursuing matters of self-interest. This reflects a more mixed legacy that is worth understanding to obtain a fuller appreciation of the history of Denmark's human rights politics and the country's gradual move towards the active and progressive role that Denmark would become known for.